Community-Oriented Training in Family Medicine: Integration in an urban residency program - Ouchterlony, David P. (1991)
Family medicine educators are challenged by the need to introduce community experiences into residency training programs. This paper describes one inner-city program's preliminary efforts to join with community-oriented health service agencies in the development of meaningful educational experiences and discusses problems and possible solutions.